2002
DOI: 10.1091/mbc.01-07-0348
|View full text |Cite
|
Sign up to set email alerts
|

Function of Dynein and Dynactin in Herpes Simplex Virus Capsid Transport

Abstract: After fusion of the viral envelope with the plasma membrane, herpes simplex virus type 1 (HSV1) capsids are transported along microtubules (MTs) from the cell periphery to the nucleus. The motor ATPase cytoplasmic dynein and its multisubunit cofactor dynactin mediate most transport processes directed toward the minus-ends of MTs. Immunofluorescence microscopy experiments demonstrated that HSV1 capsids colocalized with cytoplasmic dynein and dynactin. We blocked the function of dynein by overexpressing the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
277
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(287 citation statements)
references
References 72 publications
(141 reference statements)
6
277
0
2
Order By: Relevance
“…2). This was observed for Reovirus, Adenovirus, HSV, influenza virus and HIV 5,[42][43][44][45] . Viral transport is often highly regulated as with, for example, HSV in neurons.…”
Section: Viral Transportmentioning
confidence: 58%
See 1 more Smart Citation
“…2). This was observed for Reovirus, Adenovirus, HSV, influenza virus and HIV 5,[42][43][44][45] . Viral transport is often highly regulated as with, for example, HSV in neurons.…”
Section: Viral Transportmentioning
confidence: 58%
“…Viral transport is often highly regulated as with, for example, HSV in neurons. After fusion of incoming virions with the plasma membrane, HSV capsids are transported towards the minus end of microtubules by dynein and its cofactor dynactin 43 . In the axons of sensory neurons, incoming HSV capsids are moved by retrograde transport, whereas newly assembled capsids undergo bidirectional and salutatory motions, indicating a modulation of the plus-end directed motility 46 .…”
Section: Viral Transportmentioning
confidence: 99%
“…This transport requires intact MTs, and can be disrupted by colchicine, vinblastine or nocodazole, in both non-polarised cells [49] and sensory neurons [50]. Incoming HSV-1 capsids associate with cytoplasmic dynein and dynactin, and their transport to the nucleus is dynein dependent, since it can be blocked by the over-expression of the dynactin subunit p50 (dynamitin) [51].…”
Section: Dynein Cofactor: Dynactinmentioning
confidence: 99%
“…The relative contribution of other tegument or capsid proteins to HSV-1 transport is not known, although it has been suggested that the major tegument protein pUL36, or one of the minor capsid proteins such as pUL25, may also contribute to dynein binding in vivo [51,67]. In the case of PrV, the so-called inner tegument proteins pUL36, pUL37 and pUS3 have been shown to remain associated with the capsid during entry HSV transport and egress HSV transport and egress 39 39 [68,69].…”
Section: Dynein Cofactor: Dynactinmentioning
confidence: 99%
“…Before seeding, cells were washed and detached using 3 mM EDTA in PBS. A total of 3 3 10 4 cells was seeded into a well of a 8-chambered Lab-Tek cover glass (Nunc), coated with bovine fibronectin (Sigma Aldrich), and allowed to settle down for 3 h. Subsequently, they were incubated for another 40 min with cytochalasin D or latrunculin B (Biomol) prior to fixation and permeabilization according to the PHEMO fixation protocol (33). Cells were blocked for 30 min with 1% BSA in PBS and stained for actin and microtubules using a ORIGINAL ARTICLE monoclonal mouse-anti-a-tubulin antibody (Cell Signal), a rabbit-anti-mouse IgG coupled to Atto-633 secondary antibody (Sigma Aldrich), and phalloidin-TRITC (Invitrogen) at a concentration of 1 lg/ml.…”
Section: Cell Culture and Hiv-infectionmentioning
confidence: 99%